Party affiliations in the state legislatures : a year by year summary, 1796-2006 - Dubin, Michael J. (McFarland, 2007)
"This book lists the party affiliation of every state legislator from 1796 through the elections of 2006. Information on each state includes a summary of how its electoral process developed, including the origins and stipulations of each state's constitution, the terms and size of the legislature, and other details pertaining to the history of the state's legislative branch"--Provided by publisher